Perpetrator programmes for partner violence: are they based on ideology or evidence? - Dixon, Louise (Legal and criminological psychology, 2012)
Purpose. The ideologically based view of intimate partner violence has traditionally influenced policy and practice in modern western nations and dominated cross-national research and practice. This review considers the validity of the position statement of a British organization responsible for accrediting many male perpetrator programmes in the statutory, voluntary, and private sector as an example of this ideological influence. Method. The position statement, informed by the patriarchal view of partner violence, is evaluated using empirical evidence from various branches of the social sciences, including psychology, that have not been guided by the patriarchal view. Results. Overwhelming empirical evidence is presented, which refutes ideologically driven assumptions that have been put forward to guide current practice and evaluation of it. Conclusions. This review highlights the need to investigate intimate partner violence from a scientific and gender-inclusive perspective. The implications for psychological practice are discussed.